A prediction model for risk factors of testicular atrophy after orchiopexy in children with undescended testis - Yang, Zhilin (Transl Pediatr, 2021)
BACKGROUND: There have been limited studies with small sample sizes about risk factors of testicular atrophy. Thus, we aimed to investigate the risk factors for testicular atrophy after orchiopexy in male children with undescended testes and develop a prediction model based on clinical variables. METHODS: We performed a retrospective review of data on children who underwent orchiopexy for undescended testes from 2013 to 2017. The variables assessed included age, laterality, testicular location, preoperative testicular volume ratio, deferens and epididymis anomaly, hormonal treatment, comorbidities, type of surgical procedure, operating time, and complications as the outcome of testicular atrophy. A nomogram was constructed to predict the probability of testicular atrophy. We also validated our model based on a prospective cohort of patients who underwent orchiopexy from January 2018 to December 2018. RESULTS: A total of 1,608 patients undergoing orchiopexy were included in the training cohort. The median age was 2.8 years (range, 0.5−11.3 years). After follow-up for 12 to 18 months (median, 14 months), 228 (14.2%) cases of atrophic testes were recorded. The independent predictors of testicular atrophy were preoperative testicular volume ratio [odds ratio (OR) 0.001, P=0.001], testicular location (OR 1.903, P=0.001), deferens and epididymis anomaly (OR 6.470, P=0.001), and two-stage Fowler-Stephens orchiopexy (OR 2.613, P=0.04). Successful validation was achieved, and a receiver operating characteristic (ROC) curve was constructed. The sensitivity and specificity of the prediction model were 78.1% and 77.5%, respectively. The area under the ROC curve was 0.851. CONCLUSIONS: In patients with undescended testes, excluding those with chromosomal abnormalities and testicular nubbin, the incidence of testicular atrophy after orchiopexy is higher in patients with a lower testicular volume ratio, higher testicular location, deferens and epididymis anomaly, and in two-stage Fowler-Stephens orchiopexy. Therefore, this prediction model provides useful evidence for surgeons to choose an appropriate surgical procedure for undescended testes and predict the probability of testicular atrophy.